ComSciCon-Triangle: Regional Science Communication Training for Graduate Students - Kayleigh O’Keeffe (American Society for Microbiology, 2018)
The ability of scientists to effectively communicate their research, and scientific ideas in general, with a variety of audiences is critical in both academic and non-academic careers. There is currently a dearth of formal and informal science communication training opportunities for graduate students in science, technology, engineering, and mathematics (STEM) fields. This curriculum paper introduces ComSciCon-Triangle, a graduate student–organized science communication workshop for graduate students in STEM at research universities in the Raleigh-Durham, North Carolina, region. Started in 2015, this annual workshop aims to empower graduate students to be more engaged in communicating their research with the public as well as with fellow scientists. Each workshop consists of interactive panel discussions with invited science communicators (science writers, academics, filmmakers, etc.), informal networking opportunities with invited guests and other attendees, and hands-on sessions for improving oral and written communication skills. Analyzing pre- and post-survey data from all ComSciCon-Triangle attendees from 2015 to 2017, we find that workshop attendees feel significantly more confident in their ability to communicate scientific ideas with both the general public and with other scientists, and more confident submitting a written piece to a popular science publication or journal. We discuss how ComSciCon-Triangle serves as a model for local science communication workshops “for graduate students, organized by graduate students.”